Porous stainless steel support for hydrogen separation Pd membrane; fabrication by metal injection molding and simple surface modification. (25th May 2017) - Hwang, Kyung-Ran; Oh, Duck-Kyu; Lee, Sung-Wook; Park, Jong-Soo; Song, Myung-Hoon; Rhee, Won-Hyuk
Abstract: We prepared a disc-shaped porous stainless steel (PSS) support for hydrogen separation Pd membrane via metal injection molding (MIM) method to facilitate the mass production of porous substrates. MIMed PSS supports obtained in a batch showed relatively higher apparent porosity (from 32.75% to 39.28%) than that reported for commercially available PSS substrate. In addition, the surface morphologies of the MIMed PSS, surface roughness of 1.119 μm and pore depth of 8.6 μm, indicate its suitability as a membrane support than the commercially available one. Pd membrane prepared over MIMed PSS, which was modified by a simple axial pressing method to control the surface morphologies, had a thinner Pd layer, 2.94 μm, and showed an extremely higher ideal H2 /N2 selectivity with a hydrogen permeation flux of 21.3 ml/min/cm 2 at del-P = 1 bar and 400 °C, compared with Pd membrane over MIMed PSS modified with conventional surface modification. Highlights: Disc-shaped porous stainless steel substrates fabricated by metal injection molding. Porous stainless steel support for preparing a thin and dense Pd-based hydrogen membrane. A simple axial pressing method to control the surface morphologies of the substrates.